2016
DOI: 10.1159/000443055
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SULT2B1b Promotes Angiogenesis in Human Gastric Cancer

Abstract: Background/Aims: Overexpression of cytosolic sulfotransferase 2B1b (SULT2B1b) has been commonly found in colorectal and hepatocellular carcinoma, suggesting that SULT2B1b might act as a potential oncogenic protein. However, its clinical significance and biological role in gastric cancer progression remain largely unknown. Methods: Expressions of SULT2B1b in clinical gastric cancer (GC) samples were examined using qRT-PCR and Western blot. Results: SULT2B1b was markedly overexpressed in human GC samples, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
(37 reference statements)
0
18
0
1
Order By: Relevance
“…It has been demonstrated that SULT2B1b activity increases gastric cancer angiogenesis and tumor volume, SULT2B1b activity promotes hepatocellular carcinoma cell growth in vitro and in vivo , and SULT2B1b expression correlates with poor prognosis and promotes tumor cell growth in colorectal cancer patients. (17,18,20) In fact, the Human Protein Atlas database (http://www.proteinatlas.org/ENSG00000088002-SULT2B1/cancer) of tissue samples supports elevated expression levels of SULT2B1b in PCa compared to normal tissue. As a result of the controversial role of SULT2B1b activity, additional studies in PCa are required to fully understand its function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that SULT2B1b activity increases gastric cancer angiogenesis and tumor volume, SULT2B1b activity promotes hepatocellular carcinoma cell growth in vitro and in vivo , and SULT2B1b expression correlates with poor prognosis and promotes tumor cell growth in colorectal cancer patients. (17,18,20) In fact, the Human Protein Atlas database (http://www.proteinatlas.org/ENSG00000088002-SULT2B1/cancer) of tissue samples supports elevated expression levels of SULT2B1b in PCa compared to normal tissue. As a result of the controversial role of SULT2B1b activity, additional studies in PCa are required to fully understand its function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a potential role of SULT2B1b in the growth and progression of cancer cells(1720). SULT2B1b was studied in PCa in androgen-free conditions supplemented with DHEA(19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [ 25 ] demonstrated that SULT2B1b expression is increased in colorectal carcinoma (CRC) and CRC-derived cell lines, and SULT2B1b overexpression promotes the growth and invasion of CRC cells. SULT2B1b is significantly overexpressed in gastric cancer (GC) and SULT2B1b overexpression promoted the angiogenesis and tumor growth in a GC mice model [ 26 ]. The UALCAN database indicates that SULT2B1 expression is also upregulated in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CS may also inhibit T cell function by displacing cholesterol from cell membrane and therefore compromising T cell receptor signaling . SULT2B1b may also alter the surrounding vasculature by modulating the production of angiogenic factors such as VEGF . Thus, the high level of SULT2B1b in the prostate epithelium may not only be beneficial for the epithelium but also be important for the stability of the tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%